2012
DOI: 10.1007/978-3-642-28569-1_7
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Topic Graph Extraction and Exploration of Web Content

Abstract: We present a mobile touchable application for online topic graph extraction and exploration of web content. The system has been implemented for operation on an iPad. The topic graph is constructed from N web snippets which are determined by a standard search engine. We consider the extraction of a topic graph as a specific empirical collocation extraction task where collocations are extracted between chunks. Our measure of association strength is based on the pointwise mutual information between chunk pairs wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…We already have embedded Wikipedia's infoboxes as background knowledge but not yet integrated them into the extracted web topic graphs, cf. (Neumann and Schmeier, 2011) for some more details. If so done, we will investigate the role of Wikipedia and the like as a basis for performing disambiguation of the topic graphs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We already have embedded Wikipedia's infoboxes as background knowledge but not yet integrated them into the extracted web topic graphs, cf. (Neumann and Schmeier, 2011) for some more details. If so done, we will investigate the role of Wikipedia and the like as a basis for performing disambiguation of the topic graphs.…”
Section: Discussionmentioning
confidence: 99%
“…This part of the work has partially been presented in(Neumann and Schmeier, 2011) and hence will be described and illustrated compactly.…”
mentioning
confidence: 99%
“…In [Neumann and Schmeier, 2011] and [Neumann and Schmeier, 2012] we have shown that mobile touchable devices can be a very convenient way for realizing simple and intuitive exploratory search strategies and to provide an usable mobile device searches to "find out about something". The core idea of the underlying search strategy is:…”
Section: Introductionmentioning
confidence: 99%
“…In (Neumann and Schmeier, 2011) and (Neumann and Schmeier, 2012) we have shown that mobile touchable devices can be a very convenient way for realizing simple and intuitive exploratory search strategies and to provide an usable mobile device searches to "find out about something". The core idea of the underlying search strategy is: 1.…”
Section: Introductionmentioning
confidence: 99%